Monster - Myers, Walter Dean, 1937-; Myers, Christopher A. (New York : HarperTempest, 2001)
While on trial as an accomplice to a murder, sixteen-year-old Steve Harmon records his experiences in prison and in the courtroom in the form of a film script as he tries to come to terms with the course his life has taken.
"Amistad.".
School Library Journal.
Wilson's Junior High School.
Wilson's Senior High School.
Book Links (A.L.A.), February 2001.
Books for the Teen Age (NYPL), April 1999.
Keywords: African Americans -- Fiction; Prisons -- Fiction; Self-perception -- Fiction; Trials (Murder) -- Fiction; African Americans -- Fiction; Prisons -- Fiction; Self-perception -- Fiction; Trials (Homicide) -- Fiction